Intermetallic Evolution for Isothermal Aging Up To 2000hours on Sn-4ag-0.5cu and Sn-37pb Solders with Ni/Au Layers - Siti Rabiatull Aisha, Idris; Azmah Hanim, Mohamad Ariff; Ourdjini, Ali; Saliza Azlina, Osman (Universiti Malaysia Pahang, 2013)
Reliability of a solder joint is closely related to the intermetallic compound formation during the joining process and its evolution after exposure to heat. Throughout this paper, interfacial reactions between Sn-4Ag-0.5Cu solders and Sn-37Pb solders with electroless nickel immersion gold (Ni/Au) surface finish were studied. Few of the parameters are solder type, thickness of nickel layer and aging time. The results focused on type of intermetallic compound formed and the intermetallic thickness. Aging changed the intermetallic morphology to become rounder, bigger and more compact with time. Aged Sn-4Ag-0.5Cu solders on Ni/Au exhibit the tendency for the intermetallic to change from (Cu,Ni)6Sn5 to (Ni,Cu)3Sn4 and finally Ni3Sn4. The results also showed that, with the parameters used in this experiment, nickel thickness 3micrometer is adequate to be a good diffusion barrier up to 2000hours aging time. In Sn-37Pb, redeposition of (Au,Ni)Sn4 intermetallic start after 500hour